Ovarian function following intra-ovarian injection of platelet rich plasma in premature ovarian aging - Ishrat, Shakeela; Banu, Jesmine; Deeba, Farzana; Salam, Sharmin; Saha, Chandana; Akhtar, Arifa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Premature ovarian aging as evidenced by AMH levels less than 0.5 ng/ml is predictive of reduced success in management of infertility. The most effective treatment is in vitro fertilization which is not affordable or acceptable to most of our patients with low socioeconomic background. Intra-ovarian injection of autologous platelet rich plasma (PRP) improves the ovarian reserve markers but it remains to be seen whether it improves the pregnancy rate. Methods: This was a prospective study of 29 patients with poor ovarian reserve (age between 30-40 years, AMH<0.5 ng/ml), AFC<4 in both ovaries) who received intra ovarian injection of platelet rich plasma. The patients were followed up for one year and data was collected about clinically relevant outcomes like pregnancy. Results: Four women (13.8%) had pregnancy, of which 3 were spontaneous and one was following ovarian stimulation and intrauterine insemination. All had diagnosed clinical pregnancy, of which two women had live birth. Conclusions: Given the 13.8% rate of pregnancy within one year we can speculate that PRP injection may be a reasonable alternative to in vitro fertilization in women with diminished ovarian reserve.